Assessment of the Impact of Land Use Changes along the Floodplains of River Lamurde, Jalingo Lga, Nigeria - Oruonye, E. D (Journal of Forests, 2015)
Jalingo town has developed over the years from a simple linear settlement pattern dictated by the nature of its topography to a fast growing urban complex. The rapid growth of the town has necessitated the expansion of settlement and infrastructures to accommodate relative increases in population. River Lamurde and its tributary, River Mayo Gwoi which passes through the town and play very significant roles in the provision of water for domestic and agricultural uses also limits the growth of the town on the southern part for a long time. The construction of new roads and bridges along these rivers has in recent times opened up large areas for the construction of residential houses and intensification of agricultural activities along the river banks. These changes in land uses along the floodplain of the Lamurde river have resulted in large scale transformation of the landscape with telling consequences on the river and aquatic ecosystems. This study examines the causes and impact of land use changes along the floodplains of River Lamurde on the river system and how these impacts could be curtailed to safeguard the health and sustainability of the river system. Questionnaires were used to collect data for the study and were analyzed using simple descriptive statistics, particularly frequencies, percentages and ratios. Physical observation of the study area was undertaken to obtain first hand information on various uses along the floodplains of River Lamurde in the study area. The findings of this study shows that land use along the floodplain of river Lamurde has undergone substantial level of change from open fields and fallow lands to intensively cultivated irrigation and residential areas. The dominant land use types in the basins presently are rainfed agriculture and irrigation farming, grazing, development of residential, commercial and institutional buildings as well as indiscriminate waste disposal. The observed land use activities include, excessive water extraction, deforestation for fuel wood and other domestic uses, excessive use of chemical fertilizers and land degradation due to improper agricultural practices. These land use activities have impacted negatively on the river ecosystem. The study conclude that there is need to streamline land use activities, conserve vital ecosystems like watershed areas and maintain buffers along stream channels as a matter of policy to ensure adequate protection of aquatic fauna and sustainable water supply. The town planning authority should enforce restriction of expansion of buildings on the floodplains of the river because of their vulnerability to flood disaster. Given the increasing intensity of irrigation and chemical fertilizer usage, this study recommends the need for further study on the impact of fertilizer and irrigation on the river ecosystem.